A case report of microscopic polyangiitis presenting as diffuse pulmonary symptoms with no renal involvement - Singhvi, Shreyans D.; Singh, Preksha; Khan, Rafe; Patel, Monila; Acharya, Pavan (International Journal of Research in Medical Sciences, 2020)
Microscopic polyangiitis (MPA) is a small blood vascular disorder, but with presence of no granulomas. This is a pauci- immune disorder vessels which lead to vascular inflammation and then later, it can lead to organ microscopic polyangiitis. This disorder affects multiple organs as it is a systemic disease, but usually presents with renal dysfunction - rapidly progressive glomerulonephritis. There is a possible association of p- ANCA (antineutrophil cytoplasmic antibodies) and can help with the diagnosis of the disorder. This case report is of a 70-year-old female, who presented with symptoms of diffuse pulmonary hemorrhage. After routine blood examination, radiological examination- X ray (chest) and HRCT- thorax, routine urine examination, ANA and ANCA test, the final diagnosis of microscopic polyangiitis with no renal involvement was made. The case was given immunosuppressant therapy and the patient reported of mitigation of symptoms. This case report is unique as MPA usually presents with renal dysfunction, but in this case, the patient had particularly pulmonary involvement with completely normal renal function. This case report will help future physicians for quick diagnosis of similar cases and treatment for the same.